Concept Understanding Ability and Students Belief through Think Talk Write Learning Model Using Cube Origami Media - Indah Suryawati; Khairul Asri; Nur Ainun; Rahmani Rahmani; Rifaatul Mahmuzah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Elementary school is the main foundation in developing an understanding of mathematical concepts. If the basic understanding of students' concepts is not good or weak, students cannot solve math problems. Therefore, understanding the concept is essential to help students in learning mathematics. The teacher does not optimize the methods, strategies, or learning models in the learning process. So far, the learning process is only guided by explanations or examples of questions. As a result, when students are faced with different questions, students have difficulty solving problems. It happens because of the lack of students' conceptual understanding skills. The purpose of this study was to determine the increase in the ability to understand the concept by using origami media through the Think Talk Write (TTW) learning model. This study uses a quantitative approach, while the design used in this study is the Pre-Experiment One group pre-test and post-test design. The population in the study were all fifth-grade students at SD Negeri 42 Banda Aceh, totaling 50 students, consisting of students in class VA-1 as the Experiment class, while in class VA-2 as the Control class. Based on the analysis of research data, it is stated that the significant value (2-tailed) N-Gain score is 0.000 less than 0.05, so H0 is rejected, and Ha is accepted. Thus, it can be concluded that there is an increase in the concept understanding ability and belief taught with origami media and through the TTW model with using conventional learning.